Biotechnological production of specialty aromatic and aromatic-derivative compounds - Braga, Adelaide Correia (2022)
Aromatic compounds are an important class of chemicals with different industrial applications. They are usually produced by chemical synthesis from petroleum-derived feedstocks, such as toluene, xylene and benzene. However, we are now facing threats from the excessive use of fossil fuels causing environmental problems such as global warming. Furthermore, fossil resources are not infinite, and will ultimately be depleted. To cope with these problems, the sustainable production of aromatic chemicals from renewable non-food biomass is urgent. With this in mind, the search for alternative methodologies to produce aromatic compounds using low-cost and environmentally friendly processes is becoming more and more important. Microorganisms are able to produce aromatic and aromatic-derivative compounds from sugar-based carbon sources. Metabolic engineering strategies as well as bioprocess optimization enable the development of microbial cell factories capable of efficiently producing aromatic compounds. This review presents current breakthroughs in microbial production of specialty aromatic and aromatic-derivative products, providing an overview on the general strategies and methodologies applied to build microbial cell factories for the production of these compounds. We present and describe some of the current challenges and gaps that must be overcome in order to render the biotechnological production of specialty aromatic and aromatic-derivative attractive and economically feasible at industrial scale.